Development Of Teaching Materials For Household Financial Management Training for Women Fishermen in Tasikmadu Village - Eliza Silviana Miftakh; Tatas Ridho Nugroho (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to produce and test the feasibility of Training Materials Management of Household Financial Management in the Village Tasikmadu. This research method using Design-Based Research model. The results of the final evaluation showed that 93% -95% of the learners received excellent training evaluation results, 95% -100% of the study participants gave positive responses to the training model, 89% of the students were active in training, and 79% of the studying population had implemented financial Accounting. Based on these results, the development of teaching materials for household financial management training is ready to be implemented. Based on these results, the development of teaching materials for household financial management training is ready to be implemented. This training development is easy to apply, effective and practical, as it is developed and designed in a contextual and flexible way that is modified according to the needs and circumstances of the field. In addition, the guidebook provided in this model of financial management training has been made as attractive as possible to facilitate training activities taking into account the characteristics of female fishermen as learning citizens. So when this resource is applied it will create a fun and interesting training atmosphere.